2015
DOI: 10.1007/s00221-015-4276-y
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of digit force variability during dominant and non-dominant sustained precision pinch

Abstract: This study examined the effects of handedness on the inter-digit coordination of force variability with and without concurrent visual feedback during sustained precision pinch. Twenty-four right-handed subjects were instructed to pinch an instrumented apparatus with their dominant and non-dominant hands, separately. During the pinch, the subjects were required to maintain a stable force output at 5 N for 1 min. Visual feedback was given for the first 30 s and removed for the second 30 s. Coefficient of variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 38 publications
6
11
0
Order By: Relevance
“…This finding was in line with the previous finding from the effects of visual feedback on digit force regulation during single-digit pressing [16, 17] and two-digit pinching [10, 11]. For example, absence of visuomotor correction can reduce the irregular patterns in digit force structures compared to the condition with visual feedback [10, 11, 16, 17]. The simplified time-dependent structure of the vertical shear forces at the digits with tactile deficits reflected a decreased motor control flexibility in response to external variables.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This finding was in line with the previous finding from the effects of visual feedback on digit force regulation during single-digit pressing [16, 17] and two-digit pinching [10, 11]. For example, absence of visuomotor correction can reduce the irregular patterns in digit force structures compared to the condition with visual feedback [10, 11, 16, 17]. The simplified time-dependent structure of the vertical shear forces at the digits with tactile deficits reflected a decreased motor control flexibility in response to external variables.…”
Section: Discussionsupporting
confidence: 93%
“…Results of DFA showed that with reduced tactile sensitivity the shear force components in the vertical direction of the thumb or index finger had lower structural variability (Figure 2(a)). This finding was in line with the previous finding from the effects of visual feedback on digit force regulation during single-digit pressing [16, 17] and two-digit pinching [10, 11]. For example, absence of visuomotor correction can reduce the irregular patterns in digit force structures compared to the condition with visual feedback [10, 11, 16, 17].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Asterisks indicate p < 0.016 and n.s. indicates p > 0.1. agreement with previous reports (Li et al, 2013(Li et al, , 2015Nataraj et al, 2015).…”
Section: Mep Variability Above and Beyond Predicted CV Of Mep (Cv Diff )supporting
confidence: 94%